THE DEFINITION OF ECONOMIC EFFICIENCY OF DEVELOPMENT COSTS, CREATION, PRODUCTION AND IMPLEMENTATION OF COLLECTION MODELS OF A MODERN DOMESTIC PASSENGER CARS FOR HIGH-SPEED TRANSPORTATION - Pshinko, O. M.; Myamlin, S. V.; Barash, Yu. S.; Hnennyi, O. M.; Fediushyn, Yu. M.; Prykhodko, V. I.; Shkabrov, O. A. (Science and Transport Progress, 2005)
In article calculation of economic efficiency from realization of the project on introduction of family of models of domestic modern carriages for high speed transportations on railways of Ukraine is resulted.